KUALITAS LAYANAN, KEPUASAN DAN LOYALITAS NASABAH PADA PERUSAHAAN PERGADAIAN DI KOTA BATAM - Ichtiar, Dollmart; Nugroho , Marno (Bussman Journal : Indonesian Journal of Business and Management, 2025)
The purpose of this study aims to analyze the effect of Service Quality on Customer Loyalty through Customer Satisfaction in the financial services sector of pawnshops. Using quantitative research with customer respondents at pawnshops in Batam City. Using the Structural Equitation Model (SEM) analysis technique - Smart Pls Version 3.0 By using a questionnaire distribution to a sample of 100 respondents. Based on the results of the study, it can be explained that the higher the quality of service will have a positive impact on customer satisfaction but does not have a direct effect on Customer Loyalty, increasing customer satisfaction has a positive impact on customer loyalty. The service quality variable has a positive and significant effect on customer loyalty through customer satisfaction as an intervening variable.